2014
DOI: 10.1088/1478-3975/11/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of transport in the mammary glands

Abstract: The transport of three toxins moving from the blood stream into the ducts of the mammary glands is analyzed in this work. The model predictions are compared with experimental data from the literature. The utility of the model lies in its potential to improve our understanding of toxin transport as a pre-disposing factor to breast cancer. This work is based on a multi-layer transport model to analyze the toxins present in the breast milk. The breast milk in comparison with other sampling strategies allows us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The third term, toxin transport, is specific to breast cancer. It is suggested that increased toxin presence in the mammary tissue is a pre-disposing factor to breast cancer [23,28].…”
Section: Resultsmentioning
confidence: 99%
“…The third term, toxin transport, is specific to breast cancer. It is suggested that increased toxin presence in the mammary tissue is a pre-disposing factor to breast cancer [23,28].…”
Section: Resultsmentioning
confidence: 99%
“…A multilayer model that focused more on the properties of biologic membranes than molecular descriptors was developed to predict M/P ratios . It takes into account drug particle size and diffusion coefficient as well as a number of membrane factors.…”
Section: Prediction Of the M/p Ratiomentioning
confidence: 99%
“…A multilayer model that focused more on the properties of biologic membranes than molecular descriptors was developed to predict M/P ratios. 55 It takes into account drug particle size and diffusion coefficient as well as a number of membrane factors. This very complex model was successful in predicting the M/P ratios of three drugs that are excreted into milk by different mechanisms, including active transport with cimetidine.…”
Section: Qsar Prediction Of the M/p Ratiomentioning
confidence: 99%
“…These models have emanated from the substantial body of work on mass transport in biological tissue which has featured heavily in the literature over the past few decades. We refer the interested reader to the review by Khaled and Vafai [4] for background reading and to the recent work by the same group [5] on mass transport in mammary glands which is an excellent exemplar of a different application of mass transport in biological tissue.…”
Section: Introductionmentioning
confidence: 99%